Analisis Beban Kerja Dengan Metode Full Time Equivalent Untuk Mengoptimalkan Kinerja Karyawan Cell 31 D1 (Studi Kasus PT Panarub Industry) - Widodo, Tri; Fardiansyah, Ismail; Sari, Seftin ludfita (Journal Industrial Manufacturing, 2022)
Human resources (HR) need to be considered in a company, because HR is the most important factor in producing a quality product. Human resource management (HRM) is one of the fields of general management which includes aspects of planning, organizing, implementing and controlling. In a company, it can be said that one of the most important resources is a human being who is an employee, laborer or worker. At PT. In Panarub Industry, there are employees who are overloaded with work and some are underworked. The distribution of orders is different but the time to complete is the same so that it makes working hours increase (overtime), this causes less concentration at work and can reduce product quality. The current workload allocation from the FTE calculation results is 1 position below 1.28 and 6 positions above 1.28. The optimal need for people from the actual total FTE calculation is 156 to 163. Recommendations for PT. Panarub Industry In the D1 building, 7 people are recruited. This will have an impact on reducing the value of overtime in achieving future targets, and can minimize unwanted risks. With this research, the allocation of the performance burden of PT. Panarub Industry's employees will be in accordance with production needs and will run smoothly, so that productivity can reach the target.Keywords: Human resource management, Full time equivalent, Human Resources, Workload Allocation, Workload Analysis